Assessment of a novel alternative to conventional formocresol-zinc oxide eugenol pulpotomy for the treatment of pulpally involved human primary teeth: diode laser-mineral trioxide aggregate pulpotomy - B. SALTZMAN, M. SIGAL, C. CLOKIE, J. RUKAVINA, K. TITLEY & G. V. KULKARNI (Paediatric Dentistry, 2005)
The aim of pulpotomy therapy is to maintain a carious primary tooth until natural exfoliation by removing the coronal portion of the infected pulp while preserving the uninfected radicular tissue.